KINERJA BUMDESA DALAM PENGEMBANGAN EKONOMI KREATIF DAN KESETARAAN GENDER - NGURAH WISNU MURTHI (Universitas Mahasaraswati K. Mataram, 2023)
The purpose of this study was to analyze the factors that support and inhibit the development of village-owned enterprises (BUMDESA), the role of BUMDESA in the development of creative economic enterprises and gender equality. This study uses a qualitative analysis technique with a descriptive explanation level, namely an analysis technique that describes qualitative data in the form of the development of BUMDESA, the manifestation of the role of BUMDESA in the development of the creative economy and gender equality as well as the factors that encourage and inhibit BUMDes. The population of this study were all BUMDESAs in coastal village tourism objects in Badung Regency, using the convenience sampling method, so the samples were 4 BUMDESAs that had developed and 6 creative economies in coastal village tourism objects in Badung Regency. Data for 2022, in Badung Regency the formation and types of BUMDes businesses vary because Badung Regency is very synonymous with tourism objects and the creative economy in it, including; savings and loans, waste management, cooperatives, drinking water management, organic fertilizer management, and in tourist areas there are rental boats, bicycles and others for tourists. Here the community provides boats, bicycles for rent and is managed by BUMDESA, so the community can be involved in it. The role of BUMDESA in the creative economy sector is manifested in the form of providing capital loan assistance with conditions and low interest rates for Balinese culinary culinary businesses and fruit culinary businesses, so that these culinary businesses can increase business volume and absorb more labor, especially housewives. . Likewise, the creative economy of surfing board crafts can increase business volume more broadly. For gender equality, namely BUMDESA has the role of absorbing labor in the village, especially women so that it provides the same proportion as the role of men in the village. Many women work in BUMDes units and even as BUMDESA administrators so they can improve gender equality